Influencing organisational culture by means of employee remuneration - Stachova, Katarína; Stacho, Zdenko; Bartáková, Gabriela (Business: Theory and Practice, 2015)
The aim of this paper is to particularly define the possibilities of influencing organisational culture by means of employee remuneration. The paper will present the results of research conducted over 2010–2012. The respondent group included 340 organisations operating in the Slovak Republic. The research showed that even though 98% of the interviewed organisations realise the importance and meaning of dealing with the creation and maintenance of organisational culture, only 21–43% have defined an organisational culture strategy in writing within the organisation´s strategy.